2013
DOI: 10.1021/ic401571h
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Md3+/Md2+ Reduction Potential Studied with Flow Electrolytic Chromatography

Abstract: The reduction behavior of mendelevium (Md) was studied using a flow electrolytic chromatography apparatus. By application of the appropriate potentials on the chromatography column, the more stable Md(3+) is reduced to Md(2+). The reduction potential of the Md(3+) + e(-) → Md(2+) couple was determined to be -0.16 ± 0.05 V versus a normal hydrogen electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…By application of the appropriate potentials on the chromatography column, the more stable Md 3+ is reduced to Md 2+ . The reduction potential of the Md 3+ + eMd 2+ couple was determined to be -0.16 ± 0.05 V vs. a normal hydrogen electrode [78]; Fig. 11 (b).…”
Section: Seaborgium (Sg Z = 106)mentioning
confidence: 99%
See 1 more Smart Citation
“…By application of the appropriate potentials on the chromatography column, the more stable Md 3+ is reduced to Md 2+ . The reduction potential of the Md 3+ + eMd 2+ couple was determined to be -0.16 ± 0.05 V vs. a normal hydrogen electrode [78]; Fig. 11 (b).…”
Section: Seaborgium (Sg Z = 106)mentioning
confidence: 99%
“…Presently, preparations are under way to measure the redox potential of the hexavalent Sg [81]. In one approach, a complex and continuously working system is envisioned which consists of an electrochemistry apparatus for the potentially controlled Sg reduction [77,78] connected to a separation device like SISAK [82] for the extraction, and a flow-through liquid-scintillation detection system [59]. By means of a newly designed interface [83], this shall be coupled with a recoil separator like GARIS (Gas-filled Recoil Ion Separator) at RIKEN [84].…”
Section: Perspectivesmentioning
confidence: 99%
“…The reduction behavior of trivalent mendelevium ( 255 Md 3+ , t 1/2 = 27 min) produced in the bombardment of a 248 Cm target with 11 B beams was studied using the same flow electrolytic chromatography apparatus in Section 3.1. 102 ) After the collection of reaction products, the sample was dissolved in 0.1 M HCl and then fed into a Nafion electrode column at a flow rate of 800 µL/min. Potentials between −0.3 and −0.9 V were applied to the electrodes.…”
Section: Redox Reactions Of Heavy Actinides MD and Nomentioning
confidence: 99%
“…Before conducting the Md experiments, we confirmed that the divalent state ions were eluted with 0.1 M HCl, whereas the trivalent ions were stripped with 3.0 M HCl. 102 ) As shown in Fig. 19 , Md and europium (Eu) reduction probabilities are plotted as a function of the applied potential.…”
Section: Redox Reactions Of Heavy Actinides MD and Nomentioning
confidence: 99%
“…Advanced theoretical model calculations have already provided quantitative predictions [31]. Preparations have started to measure the redox potential of hexavalent Sg [32]; a complex and continuously working system is envisioned which consists of an electrochemistry apparatus [33,34] for the potentially controlled Sg reduction connected to a separation device like SISAK for the extraction and a flow-through liquid-scintillation detection system [35]. By means of a newly designed interface [36], this shall be coupled with a recoil separator like GARIS (Gas-filled Recoil Ion Separator) at RIKEN [37].…”
Section: Perspectivesmentioning
confidence: 99%